Spatial Patterns of Nomad Tourism in Canggu Village Bali - Utama, Christian Petra; Nuryanti, Wiendu (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2024)
Nomadic Tourism has emerged as a new trend after the Covid-19 pandemic. This tourism style involves travellers moving around and staying for certain periods in destinations that offer easily movable amenities. Canggu Village in Bali has become one of the world's most popular destinations for nomadic tourists, ranking eighth based on reviews from the nomad tourist community. In Canggu Village, nomadic tourists form spatial patterns influenced by their behaviour, types of travel, and travel patterns. This research aims to identify the behaviour of nomadic tourists in Canggu Village, Bali, and to describe the spatial patterns of Nomadic Tourism in the area. The research employs a descriptive qualitative approach, utilising methods such as observation, interviews, and documentation. The findings reveal insights into the behaviour of nomadic tourists and provide a detailed description of the spatial patterns of Nomadic Tourism in Canggu Village, Bali.